Incentive Mechanisms and Institutional Frameworks for Scaling Climate-smart Agriculture Across Different Agro-ecological Regions in India - Malathi, B.; Devojee, B.; Sahoo, T. R.; Reddy, A. R.; Prasad, J. V.; Bhaskaran, A.; Meera, Shaik N. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the period from 2022 to 2025 at ICAR-ATARI, Hyderabad, to study the impact of climate-resilient technology interventions implemented under the National Innovations in Climate Resilient Agriculture (NICRA) across different agro-ecological regions of India. An ex post facto research design was employed, covering 540 stakeholders, including 300 farmers, 90 Krishi Vigyan Kendra (KVK) personnel, and 150-line department officials from NICRA-implemented regions. Data were collected using a structured questionnaire administered on a five-point Likert scale (0–5). A Composite CSA Implementation Feasibility Index was developed by incorporating technical feasibility, cost–benefit ratio, gender inclusivity, and convergence with government schemes. The findings revealed moderate to high feasibility of CSA interventions, with overall index scores ranging from 2.98 to 3.33. Crop production interventions recorded the highest feasibility score (3.33), followed by soil quality and fertility management (3.26) and ex-situ water harvesting and efficient water use (3.19). Institutional interventions showed comparatively lower feasibility (2.98). Adoption barriers ranged from 2.52 to 3.26, with technology acceptability, limited awareness, and labour availability emerging as major constraints. Among incentive mechanisms, capacity building and market linkages ranked higher, whereas subsidies and affordable credit remained relatively weak. Custom Hiring Centres, youth farmer groups, and women self-help groups were identified as key institutional mechanisms supporting the scaling of CSA interventions.